(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
In this paper I am looking at the role of Youth Work in the conflict zone which was Northern Ireland. Firstly, by way of context I will give a brief overview of historical relationship between the jurisdictions. This is necessary in order to understand the way the jurisdictions focus began, with some common sense of purpose, and how this focus began to change as the conflict developed.